Microstructure analysis of temperature effect on magnesium alloy AZE1B and its nanocomposite (1% SiC) under high strain rate testing - Tan, Wei Jie (2014)
Many researches have been studying the properties of magnesium alloys. Its lightweight has proved to be useful in aviation and automobile industries where fuel efficiency is highly sought. In this project, the microstructure of high strain rate AZ31B and AZ31B – 1% SiC under compression subjected to different temperatures (-30°C, 25°C, 200°C) are analyzed. The specimens first have to be prepared before analyzed. The preparation of materials includes: Sectioning, Mounting, Grinding, Polishing and Etching. The microstructures of the specimens are analyzed using Optical Microscope (OM), Scanning Electron Microscope (SEM) and Energy Dispersive X-Ray Spectroscopy (EDS). It was found that AZ31B had fine porosity and secondary Mg17Al12 phases. As temperature increases, the ductility of AZ31B increases as well. As for AZ31B – 1% SiC, there were fine porosity and secondary Mg2Si phases present. The SiC nanoparticles were uniformly distributed. This reduced the grain size of the magnesium alloy. As the temperature increases, the volume of twin decreases and the ductility of AZ31B – 1% SiC increases.